The Dynamics of Islamic Law in Times of Crisis: Nigerian Muslims' Perceptions of Socially Distanced Ṣalāh During the Pandemic - Shaykh Ahmad Yahya; Abdulwahab Danladi Shittu (Hayula: Jurnal Indonesia Studi Islam Multi-disiplin, 2025)
This article examines the ethical dilemmas faced by Muslim communities in making Islamic legal (ijtihād) decisions during the COVID-19 pandemic, particularly regarding the suspension of congregational prayers to protect physical health. Focusing on the Muslim community in Nigeria, the study highlights how believers opted to postpone communal worship in mosques to preserve life while continuing individual prayers at home. Using a qualitative approach through literature review, fatwā analysis, and sociological data, the article demonstrates that the protection of life (ḥifẓ al-nafs)—a core objective in maqāṣid al-sharī‘ah—served as the religious justification for prioritizing public health. The findings reveal that Islamic legal ethics are adaptive and contextual, allowing jurisprudential flexibility in times of crisis. The article’s scholarly contribution lies in integrating maqāṣid al-sharī‘ah and Islamic legal ethics with public health principles while offering a sociological perspective on religious behavior during emergencies. It also enriches global discourse on faith-based responses to the pandemic beyond the Middle East and Southeast Asia.